Enrichment of gut-derived Fusobacterium is associated with suboptimal immune recovery in HIV-infected individuals - Lee, Soo Ching; Chua, Ling Ling; Yap, Siew Hwei; Khang, Tsung Fei; Leng, Chan Yoon; Raja Azwa, Raja Iskandar; Lewin, Sharon R.; Kamarulzaman, Adeeba; Woo, Yin Ling; Lim, Yvonne Ai Lian; Loke, P'ng; Rajasuriar, Reena (Nature Research, 2018)
We explored the gut microbiota profile among HIV-infected individuals with diverse immune recovery profiles following long-term suppressive ART and investigated the relationship between the altered bacteria with markers of immune dysfunction. The microbiota profile of rectal swabs from 26 HIV-infected individuals and 20 HIV-uninfected controls were examined. Patients were classified as suboptimal responders, sIR (n = 10, CD4 T-cell <350 cells/ul) and optimal responders, oIR (n = 16, CD4 T-cell >500 cells/ul) after a minimum of 2 years on suppressive ART. Canonical correlation analysis(CCA) and multiple regression modelling were used to explore the association between fecal bacterial taxa abundance and immunological profiles in optimal and suboptimal responders. We found Fusobacterium was significantly enriched among the HIV-infected and the sIR group. CCA results showed that Fusobacterium abundance was negatively correlated with CD4 T-cell counts, but positively correlated with CD4 T-cell activation and CD4 Tregs. Multiple linear regression analysis adjusted for age, baseline CD4 T-cell count, antibiotic exposure and MSM status indicated that higher Fusobacterium relative abundance was independently associated with poorer CD4 T-cell recovery following ART. Enrichment of Fusobacterium was associated with reduced immune recovery and persistent immune dysfunction following ART. Modulating the abundance of this bacterial taxa in the gut may be a viable intervention to improve immune reconstitution in our setting.